Bibliometric Analysis of the Philosophy Scientific Production indexed by Scopus: A Comparative Perspective in Ibero-America - León Cano, Juan Fernando; Ordóñez, Edward Javier; González Osorio, María Fernanda (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The goal of this study was to conduct a bibliometric analysis of the philosophy scientific production of Ibero-American journals indexed by Scopus during the period from 2016 to 2020. Method: To do so, data was extracted from the SCImago Journal & Country Rank website where Lotka’s Law was used to identify citations in relation to authors. We also identified the most significant authors, journals, and countries in terms of philosophy scientific production and the participation of women in the editorial boards of the selected journals. Results: the period between 2016 and 2020, the 38 selected Ibero-American journals produced a total of 5,232 texts. The 38 selected journals belonged to the following Ibero-American countries: Spain (17), Brazil (5), Mexico (4), Colombia (4), Chile (3), Portugal (2), Argentina (1), Peru (1), and Venezuela (1), which shows that Spain comprises 45% of the journals and 50% of the production in the region. Conclusions: Scientific production in Ibero-America is low.